2020
DOI: 10.1126/science.aaw9270
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an edge supercurrent in the Weyl superconductor MoTe 2

Abstract: Edge supercurrents in superconductors have long been an elusive target. Interest in them has reappeared in the context of topological superconductivity. We report evidence for the existence of a robust edge supercurrent in the Weyl superconductor molybdenum ditelluride (MoTe2). In a magnetic field B, fluxoid quantization generates a periodic modulation of the edge condensate observable as a “fast-mode” oscillation of the critical current Ic versus B. The fast-mode frequency is distinct from the conventional Fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 21 publications
3
78
0
1
Order By: Relevance
“…Specifically, a CDW can fold four WPs in a rotation-and Tsymmetric WSM into an eightfold double Dirac point (DDP) in which line defects bind helical modes equivalent to HOTI hinge states [125,126]; alternatively, a DDP critical point can also be realized by coupling two fourfold Dirac points with a CDW. Recent experiments have demonstrated hinge-statelike step-edge helical modes and robust edge supercurrents in rotation-and T -symmetric WSMs [127][128][129][130][131], as well as a stable DDP and topological step-edge modes in the CDW phase of TaTe 4 [132]. In the SM, we present an explicit model demonstrating that a T -symmetric Dirac-CDW hosts an eightfold DDP critical point that separates weak TI (WTI) and "obstructed" WTI (oWTI) phases that differ by a helical HOTI.…”
mentioning
confidence: 99%
“…Specifically, a CDW can fold four WPs in a rotation-and Tsymmetric WSM into an eightfold double Dirac point (DDP) in which line defects bind helical modes equivalent to HOTI hinge states [125,126]; alternatively, a DDP critical point can also be realized by coupling two fourfold Dirac points with a CDW. Recent experiments have demonstrated hinge-statelike step-edge helical modes and robust edge supercurrents in rotation-and T -symmetric WSMs [127][128][129][130][131], as well as a stable DDP and topological step-edge modes in the CDW phase of TaTe 4 [132]. In the SM, we present an explicit model demonstrating that a T -symmetric Dirac-CDW hosts an eightfold DDP critical point that separates weak TI (WTI) and "obstructed" WTI (oWTI) phases that differ by a helical HOTI.…”
mentioning
confidence: 99%
“…Guguchia et al observed the two-gap s-wave symmetry of the superconducting order parameter in T d -MoTe 2 , and suggested a higher possibility of a topologically non-trivial s +− state in T d -MoTe 2 [ 40 ]. A fast-mode oscillation of the critical current I c versus magnetic field B along the edge was observed in T d -MoTe 2 by Wang et al, which was generated by fluxoid quantization and indicated the existence of a robust edge supercurrent [ 41 ]. As the breaking of the time-reversal symmetry or inversion symmetry is the prerequisite for WSM, T d -MoTe 2 was predicted as a Type-II WSM due to its noncentrosymmetric lattice structure [ 26 ].…”
Section: Phases and Properties Of Motementioning
confidence: 99%
“…Moreover, monolayer 2H MoTe 2 provides a great platform for developing phase-change devices because of the reversible phase transition of monolayer 2H to 1T′ MoTe 2 12 . The 1T′ MoTe 2 is the Weyl superconductor with an edge supercurrent 15 , and monolayer 1T′ is a quantum spin Hall insulator 16 . shows hexagonal shape, a typical shape of 2H single crystals (with size ranging from a few to tens of micrometers, Fig.…”
Section: Read Full License Main Textmentioning
confidence: 99%